Localization of mannoprotein in Cryptococcus neoformans. - Vartivarian, S E (1989)
Cell wall mannoprotein of nonpathogenic yeasts is surface exposed, since the cells are agglutinated by concanavalin A and antimannoprotein antibodies. However, nonencapsulated cells of Cryptococcus neoformans were agglutinated neither by concanavalin A nor by antimannoprotein antibodies. Immunogold electron microscopy located most mannoprotein in the inner cell wall. Chemical analysis of purified cell walls showed the lack of mannose, xylose, and galactose residues. These data indicate that cryptococcal mannoprotein recovered from the cultural supernatant is a nonstructural element of the cell wall.